The Bibliography of the Academician Nenad Cambi (Archaeologia Adriatica, 2008)
The second issue of the journal Archaeologia Adriatica is in honor of the Academician Nenad Cambi, and hence a bibliography of all his works is published in this issue. The bibliography covers the period from 1960 to 2007, meaning from his first published work to the present day. In this cited period, the Academician Cambi published 378 bibliographic units.The works are divided into categories according to content and according to the type of publication in which they were printed. Within each category, the bibliographic units are arranged in chronological order according to the year of publication.
Keywords: Nenad Cambi; bibliography